2017
DOI: 10.1080/02755947.2017.1317677
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics Models to Estimate Numbers of Larval Lampreys Consumed by Smallmouth Bass in Elk Creek, Oregon

Abstract: Nonnative fishes have been increasingly implicated in the decline of native fishes in the Pacific Northwest. Smallmouth Bass Micropterus dolomieu were introduced into the Umpqua River in southwest Oregon in the early 1960s. The spread of Smallmouth Bass throughout the basin coincided with a decline in counts of upstream‐migrating Pacific Lampreys Entosphenus tridentatus. This suggested the potential for ecological interactions between Smallmouth Bass and Pacific Lampreys, as well as freshwater‐resident Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 55 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…Changing the proportion of an individual prey item alters the proportions of all other prey; therefore, we altered the counts of each prey item in the diet by ±25%, which redistributed proportions to all other prey (e.g., Schultz et al. ). Energy densities of major prey items were varied by ±20%. Mortality and population size based on estimated lower and upper 95% CIs were modeled; for age‐0 and age‐1 fish, we allowed values to vary by a coefficient of variation of 20% (maximum annual mortality was set to 0.99). Temperature experience was modeled by using the behavioral thermoregulation scenario.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the proportion of an individual prey item alters the proportions of all other prey; therefore, we altered the counts of each prey item in the diet by ±25%, which redistributed proportions to all other prey (e.g., Schultz et al. ). Energy densities of major prey items were varied by ±20%. Mortality and population size based on estimated lower and upper 95% CIs were modeled; for age‐0 and age‐1 fish, we allowed values to vary by a coefficient of variation of 20% (maximum annual mortality was set to 0.99). Temperature experience was modeled by using the behavioral thermoregulation scenario.…”
Section: Methodsmentioning
confidence: 99%
“…Consumption of prey items (e.g., Amphipoda, Decapoda, and zooplankton) was altered by ±25%. Changing the proportion of an individual prey item alters the proportions of all other prey; therefore, we altered the counts of each prey item in the diet by ±25%, which redistributed proportions to all other prey (e.g., Schultz et al 2017). 14.3 10.9 9.3 11.0 11.5 275 5.0 5.0 5.0 5.0 5.0 90 2.…”
Section: Taxonmentioning
confidence: 99%
“…In fact, direct control of Smallmouth Bass may only exacerbate its impacts on receiving ecosystems due to strong compensatory responses to many forms of removal (Zipkin et al, 2008). This case emphasizes exogenous factors as important interaction modifiers, although less research has been dedicated to endogenous factors that could affect impacts (e.g., body size; Lawrence et al, 2015;Schultz et al, 2017).…”
Section: Protect Cold Watermentioning
confidence: 99%
“…In the Columbia River near Richland (WA, USA), each Smallmouth Bass and Northern Pikeminnow (Ptychocheilus oregonensis) were estimated to consume 1.0-1.4 and 0.3-0.6 salmonids daily respectively (Tabor, Shively, & Poe, 1993). A recent research from Southern Oregon suggested that Smallmouth Bass poses a high predation threat to lamprey larvae and negatively impacts the lamprey population (Schultz et al, 2017). However, information on the extent and magnitude of larvae predation by various fishes is still very limited.…”
Section: One Of the Most Obvious Causes Of Decline For Anadromousmentioning
confidence: 99%